THE EFFECTS OF READING HABIT TOWARDS STUDENTS’ READING COMPREHENSION AT PRIVATE SENIOR HIGH SCHOOLIN PURWAKARTA - Asep Suhana; Acep Haryudin (STKIP Siliwangi, 2017)
The purpose of this research is to find out the effects of reading habit towards student’s reading comprehension. The method used is survey method. Samples were 80 students with a simple random technique. The data was collected by distributing questionnaires directly to the sample. Data analysis using descriptive statistics and the research was conducted on March to July 2015.The result showed: 1). There are any significant effects of reading habit towards students’ reading comprehension. That is proved by value of Fo 33,221 and sig 0,000 < 0,05. The results of correlation analysis of multiple correlation coefficient obtainedbyRy12=0.681and coefficient determination= 46,3 %. While from the regression analysis obtained the regression equation of multiple regression . 2). There is a significant effect of reading habit towards students’ reading comprehension. That is proved by the value of tobserve = 4.926 and Sig. 0.000 < 0.05. 3).